Savior Siblings Might Rescue Fetal Lethality But Not Adult Lymphoma in Irf2bp2-Null Mice - Vilmundarson, Ragnar O.; Heydarikhorneh, Niloufar; Duong, An; Ho, Tiffany; Keyhanian, Kianoosh; Soheili, Fariborz; Chen, Hsiao-Huei; Stewart, Alexandre F. R. (Frontiers in Immunology, 2022)
Interferon regulatory factor 2 binding protein 2 (Irf2bp2), a co-repressor of Irf2, is required for fetal hepatic erythropoiesis through the expansion of erythromyeloid progenitors. Mice with germline ablation of the entire Irf2bp2 transcript produced no viable Irf2bp2-null pups in first litters. In subsequent litters, fewer than 1/3 of the expected Irf2bp2-null pups were born and half survived to adulthood. As in humans with somatic mutations in IRF2BP2, adult Irf2bp2-null mice developed lymphoma. Transcriptome profiling of liver, heart, and skeletal muscle from Irf2bp2-null adult mice revealed a predominant upregulation of interferon-responsive genes. Of interest, hematopoietic stem cell-enriched transcription factors (Etv6, Fli1, Ikzf1, and Runx1) were also elevated in Irf2bp2-null livers. Intriguingly, Irf2bp2-positive myeloid (but not lymphoid) cells were detected in the livers of adult Irf2bp2-null mice. In female Irf2bp2-null mice, these cells carried a Y chromosome while in male Irf2bp2-null livers, no cells with Barr bodies (inactivated X chromosomes) were detected, indicating that Irf2bp2-positive erythromyeloid cells might be acquired only from male siblings of prior litters by transmaternal microchimerism. These cells likely rescue the deficit in fetal erythropoiesis, but not adult-onset lymphomagenesis, caused by Irfb2p2 ablation.